Weak localization, Aharonov–Bohm oscillations and decoherence in arrays of quantum dots - Golubev, D.S.; Semenov, A.G.; Zaikin, A.D. (Физика низких температур, 2010)
Combining scattering matrix theory with non-linear σ-model and Keldysh technique we develop a unified theoretical approach enabling one to non-perturbatively study the effect of electron–electron interactions on weak localization and Aharonov–Bohm oscillations in arbitrary arrays of quantum dots. Our model embraces weakly disordered conductors, strongly disordered conductors and (iii) metallic quantum dots. In all these cases at T→0 the electron decoherence time is found to saturate to a finite value determined by the universal formula which agrees quantitatively with numerous experimental results. Our analysis provides overwhelming evidence in favor of electron–electron interactions as a universal mechanism for zero temperature electron decoherence in disordered conductors.